Penerapan Metode Six Sigma pada Proses Produksi Injection Molding Tipe X di PT. ABC - Bela, Anisa; Ratnasari, Lisa (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Masterpen is one of the types of ballpoint pens that experiences stable demand every month, necessitating consistent production quality to meet predetermined standards. In its production process, PT Zebra Asaba Industries involves several departments, one of which is the injection department. During the production process in the injection department, the components of Masterpen, specifically the lower stick of Masterpen, often suffer from product defects. Observations have revealed a 16% defect rate in the production output, comprising 61% flash defects, 23% silver defects, and 16%barrel defects. This research aims to delve into the underlying factors causing defects in the Red Masterpen Lower Stick product at PT Zebra Asaba Industries. The research employs the Six Sigma method. The results show that the DPMO (Defects Per Million Opportunities) value for flash defects is 47,885.57 with a Sigma level of 3.17, while for silver defects, the DPMO value is 18,034.83 with a Sigma level of 3.59.